Disruption of the Serine/Threonine Kinase Akt Gene Affects Ovarian Development and Fecundity in the Cigarette Beetle, Lasioderma serricorne - Xu, Kang-Kang; Yan, Yi; Yan, Shu-Yan; Xia, Peng-Liang; Yang, Wen-Jia; Li, Can; Yang, Hong (Frontiers in Physiology, 2021)
Serine/threonine kinase Akt, an important component of the insulin signaling pathway, plays an essential role in many physiological processes. In this study, we identified and characterized an Akt gene (designated LsAkt) from the cigarette beetle, Lasioderma serricorne. LsAkt contains a 1614 bp open reading frame encoding a 537 amino acid protein that possesses a conserved pleckstrin homology domain and a serine/threonine kinase domain. The expression of LsAkt was high in pupal stages and peaked in day-4 female pupae. In adult tissues, LsAkt was highly expressed in the thorax, ovary, and midgut. The expression of LsAkt was induced by methoprene or bovine insulin in vivo, but significantly decreased by 20-hydroxyecdysone. RNA interference-mediated knockdown of LsAkt resulted in severely blocked ovarian development and reduced fecundity and hatchability. The vitellogenin (Vg) content and juvenile hormone (JH) titers of LsAkt-depletion beetles were decreased, and expressions of Vg and four JH signaling and biosynthetic genes were significantly decreased. Silencing of LsAkt reduced the amounts of glucose, glycogen, and trehalose in female adults and affected the expressions of seven key carbohydrate metabolic genes. Taken together, it is inferred that Akt implicates in L. serricorne reproduction by modification of Vg synthesis, juvenile hormone production and carbohydrate metabolism.